EFFECT EVALUATION OF SODIUM PYRROLIDONE CARBOXYLIC ACID (NA PCA) ON THE ASTAXANTHIN NANOEMULSION FORMULATION STABILITY - Nadia Sofiani, Anastasia
Photoaging is a phenomenon that often occurs on the skin due to excess UV exposure. Photoaging can be prevented by using antioxidants. Astaxanthin is a material that has good antioxidant abilities. In order to prevent skin photoaging, asthaxanthin can be formulated in topical nanoemulsion dosage form and applied to the skin. One excipient that is widely used in topical formulations is Sodium Pyrrolidone Carboxylic Acid (Na PCA) as a moisturizer. This study aims to evaluate the effect of Na PCA on the stability of the formulated nanoemulsions that have been developed using the Box-Behnken design. The factors used in the Box-Behnken design are surfactant concentration, surfactant-cosurfactant ratio, and oil concentration. Meanwhile, the responses evaluated are the globule diameter (nm) and the polydispersity index. The optimum formula obtained consists of a total oil concentration of 3.67%, a surfactant concentration of 2.09% with a GSC-tween 20 ratio of 2.15:1, 0.5% phenoxyethanol, astaxanthin 0.07%, and aqua dm 93.67%. Evaluation of the physical and chemical characteristics of the nanoemulsion was conducted for organoleptic assessment, pH, astaxanthin content, encapsulation efficiency, globule diameter, polydispersity index, zeta potential, in vitro occlusion test, freeze thaw, and stability testing. This study showed that Na PCA, with concentration of 0.5%, that was added to the optimum formula was able to increase stability of the astaxanthin nanoemulsion.